Use of monoclonal antibody against human neutrophil elastase in normal and leukaemic myeloid cells. Issue 8 (August 1988) - Pulford, K A; Erber, W N; Crick, J A; Olsson, I; Micklem, K J; Gatter, K C; Mason, D Y
Abstract : A monoclonal antibody, NP57, was produced and used against the neutrophil granule protein elastase, which selectively stain neutrophils in cryostat and paraffin wax sections. The antibody stains neutrophils and a subpopulation of monocytes in blood smears and neutrophil precursors in bone marrow smears, and gives positive reactions with the cell lines HL60 and U-937. It labelled the blast cells in 68% of cases of acute myeloid leukaemia (M1-M5) but was unreactive with all cases of lymphoid leukaemias. Most of the elastase negative myeloid leukaemias were labelled by monoclonal anti-myeloperoxidase (antibody MPO-7) as were cells from the promyelocytic line HL60. No cases of myeloid leukaemia showed the opposite pattern–that is elastase positive, myeloperoxidase negative, suggesting that the production of myeloperoxidase precedes the onset of elastase synthesis during myeloid maturation. The anti-elastase antibody NP57 is a useful addition to the range of monoclonal antibodies available for the differential diagnosis of acute leukaemia by alkaline phosphatase-antialkaline phosphatase (APAAP) labelling of cell smears; it may also be of value for the histopathological diagnosis of tumour deposits in myeloid leukaemia and for the detection of neutrophils in paraffin sections.